IMPLEMENTATION OF DIGITAL MARKETING ON CONSUMERS SEMBILAN PULUH DERAJAT COFFEE PEMATANG SIANTAR - Marisi Butarbutar; Efendi Efendi; Rosita Manawari Girsang; Rosalinda Septiani Sitompul; Fenny Aulia Manik (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to analyze the implementation of digital marketing in consumers of Sembilan Puluh Derajat Â Coffee Pematang Siantar. Research methods with surveys, data collection through interviews and questionnaires. The unit of analysis in this study was 40 consumers. The data is analyzed by qualitative analysis. The results showed that digital marketing was good but not optimal, with the highest dimension in the interactive advertising dimension, and the lowest value in the viral marketing dimension. To optimize the implementation of digital marketing by involving influencers to work together to introduce their products to consumers.